2008
DOI: 10.1097/qai.0b013e3181775926
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster-Randomized Trial of Provider-Initiated (Opt-Out) HIV Counseling and Testing of Tuberculosis Patients in South Africa

Abstract: Objective-To determine whether implementation of provider-initiated HIV counseling would increase the proportion of tuberculosis patients that received HIV counseling and testing. Design-Cluster-randomized trial with clinic as unit of randomizationSetting-Twenty, medium-sized primary care TB clinics in the Nelson Mandela Metropolitan Municipality, Port Elizabeth, Eastern Cape Province, South Africa Subjects-A total of 754 adults (≥ 18 years) newly registered as tuberculosis patients the twenty study clinics In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 5 publications
5
38
0
Order By: Relevance
“…[31][32][33][34][35] Although data from Botswana suggest that introducing PITC into primary care clinics increased the uptake of HIV testing, 22,36-39 the country's small population and status as a middle-income country make the findings difficult to generalize. Additional supporting evidence for the effectiveness of PITC in outpatient settings in sub-Saharan Africa comes from experience in tertiary health-care in Uganda 23,40 and South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35] Although data from Botswana suggest that introducing PITC into primary care clinics increased the uptake of HIV testing, 22,36-39 the country's small population and status as a middle-income country make the findings difficult to generalize. Additional supporting evidence for the effectiveness of PITC in outpatient settings in sub-Saharan Africa comes from experience in tertiary health-care in Uganda 23,40 and South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…To date, evidence that PITC can improve case-finding of HIV+ patients and increase the number who proceed to HIV treatment and care has come primarily from controlled studies 25,31,32 and from specific intervention programmes: for example, studies targeting patients with tuberculosis or sexually transmitted infections or programmes to prevent mother-to-child transmission of HIV. [31][32][33][34][35] Although data from Botswana suggest that introducing PITC into primary care clinics increased the uptake of HIV testing, 22,36-39 the country's small population and status as a middle-income country make the findings difficult to generalize.…”
Section: Discussionmentioning
confidence: 99%
“…15,[42][43][44] A cluster randomized trial conducted in tuberculosis clinics in South Africa in 2005 found that the introduction of opt-out PITC increased the uptake of HIV testing by 13.7%, from 6.5% when HIV testing was carried out on an opt-in basis to 20.2% with opt-out PITC. 45 The 2011 WHO report on global tuberculosis control stated that HTC is now standard for tuberculosis patients in many countries, especially in Africa. In 2010, more than 75% of tuberculosis patients knew their HIV status in 68 countries and territories, including 22 countries in the WHO African Region.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, this strategy was shown to significantly increase testing uptake (20.2% among intervention clinics versus 6.5% among control clinics; P = 0.009) in South Africa. 19 However, in this study, most persons remained untested (79.3%) because TB staff failed to offer counseling. A similar approach of opt-out HIV testing in Zambia was somewhat more successful, but still low with HIV testing in 50% of TB patients.…”
Section: Introductionmentioning
confidence: 96%